Real time availability and consistency of health-related information across multiple stakeholders: A blockchain based approach - Dodevski, Zlate; Filiposka, Sonja; Mishev, Anastas; Trajkovikj, Vladmir (My University, 2021)
Sensitivity of the health-related data and the focus on compliance and security has traditionally emphasized the need for centralized approach while implementing Electronic Health Records (EHR) systems. These one-institutional architectural designs are leading to fragmented and scattered pieces of valuable data across various data warehouses and silos. Interoperability challenges arise due to the absence of unified data management and exchange mechanisms making the social need for fundamental design changes bigger. The capability of a distributed ledger technology and blockchain to offer immutable, decentralized and cryptographically secured record of transactions throughout a peer-to-peer network can facilitate better collaboration and increased interoperability in the field of health and insurance information exchange processes. The paper examines different approaches and application of blockchain technology and identifies which implementations of components are more suitable and beneficial for the specific eco-system analyzed in the paper. This paper presents alternative way of dealing with information exchange across multiple stakeholders by justifying the use of decentralized approach, distributed access and solution how to comprehensively track and assemble health related data. We propose an architectural design and overview of a specific use case with focus on information exchange processes between health insurance providers and health care organizations, by using blockchain as an underlying technology. The architectural overview and data flows, backed up by sequence diagrams from specific use cases offered in this paper, can serve as a guide to the blockchain technology adoption and initial setup.
Keywords: blockchain, health-related data, health information exchange, health insurance, decentralization